Lime and gypsum reduce N-fertilizer requirements and improve soil physics, fertility and crop yields in a double-cropped system - Andrade, Maria Gabriela de Oliveira [UNESP]; Cordeiro, Carlos Felipe dos Santos [UNESP]; Roberto, Amanda Ferraresi [UNESP]; Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP] (Elsevier, 2025)
The synergistic effects of soil acidity alleviation and nitrogen (N) fertilization on soil physical attributes and their impacts on crop yields in highly weathered soils have not been assessed. The study was carried out in southeastern Brazil, in a tropical climate environment, in a sandy clay textured Oxisol. In total there were 12 treatments, that investigated the effects of surface application of lime, phosphogypsum, and N fertilization on soil chemical and physical attributes and soybean and maize nutrition and yield in two seasons (2020–2022). The treatments consisted of a control (no lime or, phosphogypsum), lime (2.9 Mg ha−1), and lime + phosphogypsum (2.0 Mg ha−1) combined with four different N rates applied to maize (0, 80, 160 and 240 kg ha−1). Lime and gypsum increased maize and soybean yields, especially under low N input. Lime and gypsum enhanced soil aggregate stability up to a depth of 60 cm and increased aggregate size up to a depth of 40 cm at N rates of up to 160 kg ha−1. Lime and gypsum also increased soil surface and subsurface pH and soil calcium and magnesium levels up to a depth of 60 cm, particularly under low N input. Moreover, lime and gypsum increased soil organic matter content in both the surface and subsurface layers, particularly under high N input. Overall, our findings emphasize the benefits of combining lime and gypsum with moderate input of N-fertilizer for improving crop yields through enhanced soil physical and chemical properties.
Keywords: Liming; Phosphogypsum; Soil attributes; Soil management; Tropical no-till